Effect of Nitrogen on the Growth and Yield of Carrot (Daucus carota L.) (The Agriculturists, 2013)
An experiment was carried out at farmers field in Debigonj, Panchagorh during November 2009 to February 2010 to evaluate the effect of four levels of applied nitrogen on the growth and yield of carrot. The experiment was laid out in a Randomized Complete Block Design with three replications. The maximum plant height (47.36 cm), root length (16.17 cm), fresh weight of leaves (145.1 g), dry matter content (11.66 g) of leaves, fresh weight of root (68.33 g), dry matter content of root (15.90%), gross yield (22.55 t/ha) and marketable yield (20.67 t/ha) were found in 100 kg N/ha. DOI: http://dx.doi.org/10.3329/agric.v11i1.15246 The Agriculturists 2013; 11(1) 76-81